2018
DOI: 10.1080/13632752.2018.1461470
|View full text |Cite
|
Sign up to set email alerts
|

“You have to do something beyond containing”: developing inclusive systems in a partnership of primary schools

Abstract: Being of Maori heritage, Jill has a particular interest in culturally appropriate provisions for Mäori children with special needs, gifted education, and the education of learners with ASD and parent voice. "You have to do something beyond containing": Developing inclusive systems in a partnership of primary schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Sikes et al (2007) suggest that inclusion is often not viewed positively for those who present challenging behaviour. Gazeley et al (2015), however, directly link inclusive practices to reducing FTEs and contrastingly Rose et al (2018) found that a group of schools working collaboratively to reduce FTEs succeeded in developing more inclusive systems. There is, therefore, clearly a relationship between inclusive practice and exclusion.…”
Section: )mentioning
confidence: 98%
“…Sikes et al (2007) suggest that inclusion is often not viewed positively for those who present challenging behaviour. Gazeley et al (2015), however, directly link inclusive practices to reducing FTEs and contrastingly Rose et al (2018) found that a group of schools working collaboratively to reduce FTEs succeeded in developing more inclusive systems. There is, therefore, clearly a relationship between inclusive practice and exclusion.…”
Section: )mentioning
confidence: 98%